2014
DOI: 10.1094/phyto-12-13-0346-r
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of an Experimental Population of Phytophthora capsici in the Field

Abstract: Populations of the vegetable pathogen Phytophthora capsici are often highly diverse, with limited gene flow between fields. To investigate the structure of a newly established, experimental population, an uninfested research field was inoculated with two single-zoospore isolates of P. capsici in September 2008. From 2009 through 2012, ≈50 isolates of P. capsici were collected from the field each year and genotyped using five microsatellite loci. The same two isolates were also crossed in the lab. High levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 50 publications
4
22
0
Order By: Relevance
“…These in vitro isolates served as a reference for the field isolates, for which generation was a priori unknown. Three of the in vitro progeny were identified as putative selfs by Dunn et al (2014), which was confirmed by our analysis (see ‘Selfing in the lab and field’), and are hereafter referred to as in vitro selfs to distinguish them from the in vitro F 1 progeny. The A1 (isolate: 0664-1) and A2 (isolate: 06180-4) founding parents were genotyped 14 and 11 times, respectively, to estimate laboratory and genotyping errors (Supplementary Table S2).…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…These in vitro isolates served as a reference for the field isolates, for which generation was a priori unknown. Three of the in vitro progeny were identified as putative selfs by Dunn et al (2014), which was confirmed by our analysis (see ‘Selfing in the lab and field’), and are hereafter referred to as in vitro selfs to distinguish them from the in vitro F 1 progeny. The A1 (isolate: 0664-1) and A2 (isolate: 06180-4) founding parents were genotyped 14 and 11 times, respectively, to estimate laboratory and genotyping errors (Supplementary Table S2).…”
Section: Resultssupporting
confidence: 73%
“…Exposure to mating type specific hormones (α1 and α2) stimulates production of the gametangia, subsequent outcrossing, and formation of recombinant oospores (Ko, 1988). However, both mating types produce both male and female gametangia, and thus are capable of self-fertilization (Shattock, 1986; Ko, 1988), which is thought to occur at a lower rate relative to outcrossing in P. capsici (Uchida and Aragaki, 1980; Dunn et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…oryzicola [25]). Studies investigating population structure on a small geographical scale have seldom been realized for plant-associated bacteria or for plant-associated oomycetes and fungi (22,(26)(27)(28).…”
Section: Importancementioning
confidence: 99%
“…Markers with high mutation rates such as microsatellites (also known as simple sequence repeats or SSRs) provide insights into recent divergence (Atallah et al 2010;Baumgartner et al 2010;Berbegal et al 2013;Dunn et al 2014;Dutech et al 2010;Goss et al 2009b), whereas mitochondrial, nuclear or other sequence loci provide inferences about the more distant evolutionary history given the slower mutation rates Goss et al 2009a;Malvarez et al 2007;Schoebel et al 2014;Stukenbrock et al 2007).…”
Section: Choosing and Using Molecular Markersmentioning
confidence: 99%